2009
DOI: 10.1099/vir.0.007385-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the entire genomes of torque teno midi virus variants in chimpanzees: infrequent cross-species infection between humans and chimpanzees

Abstract: Humans are frequently infected with three anelloviruses which have circular DNA genomes of 3.6-3.9 kb [Torque teno virus (TTV)], 2.8-2.9 kb [Torque teno mini virus (TTMV)] and 3.2 kb [a recently discovered anellovirus named Torque teno midi virus (TTMDV)]. Unexpectedly, human TTMDV DNA was not detectable in any of 74 chimpanzees tested, although all but one tested positive for both human TTV and TTMV DNA. Using universal primers for anelloviruses, novel variants of TTMDV that are phylogenetically clearly separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…In the gel electrophoresis expected 431 base pair product for SAV2 and 441 bp product for SAV1 ( 4 , 8 ) were observed ( Figure 1 ). Alignment of the seven obtained sequences (GenBank accession numbers: KC352905, KC352906, KC352907, KC352908, KC352909, KC352910, KC352911) revealed a high degree of genetic variability among the TTMDV/SAV DNA (homology ranging from 70% to 93%) with some sequences in the Gen Bank.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In the gel electrophoresis expected 431 base pair product for SAV2 and 441 bp product for SAV1 ( 4 , 8 ) were observed ( Figure 1 ). Alignment of the seven obtained sequences (GenBank accession numbers: KC352905, KC352906, KC352907, KC352908, KC352909, KC352910, KC352911) revealed a high degree of genetic variability among the TTMDV/SAV DNA (homology ranging from 70% to 93%) with some sequences in the Gen Bank.…”
Section: Resultsmentioning
confidence: 96%
“…In 2007, Ninomyia et al identified a novel DNA virus with a genomic organization resembling those of TTV and TTMV and designated this new virus as Torque Teno Midi Virus (TTMDV), they also showed that Small Anellovirus (SAV1) and SAV2 were deletion mutants or artifacts generated during the amplification of TTMDV ( 3 ). Therefore, these viruses were named TTMDV/SAV and then TTMDV viruses and were classified as Gammatorquevirus genus (including 15 species: Torque teno midi virus 1 - 15) of the family ( 1 - 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…ORF2 encodes 111 amino acids and shares no amino acid sequence identity with proteins in GenBank. ORF2 lacks the motif W-X 7 -H-X 3 -C-X 1 -C-X 5 -H that is conserved among TTVs, TTMVs and TTMDVs (Hijikata et al , 1999; Ninomiya et al , 2007, 2009; Okamoto et al , 2000; Takahashi et al , 2000). ORF3 encodes 204 amino acids, and shares weak amino acid sequence identity (16 %) with ZcAV ORF3 only, indicating that SealAV could be more closely related to ZcAV than to other anelloviruses.…”
Section: Full Textmentioning
confidence: 99%
“…Human anelloviruses were first discovered in 1997 and have been classified into three genera in the family Anelloviridae : TTV, genus Alphatorquevirus ; TTMV, genus Betatorquevirus ; and torque teno midi virus (TTMDV), genus Gammatorquevirus 36 37 . Their genomes consist of small, single-stranded circular DNA, and their capsids have no lipid envelopes.…”
Section: Discussionmentioning
confidence: 99%